Analisis Service Quality dan Store Layout terhadap Customer Satisfaction pada Borma Cabang Permata Cimahi - Elan Rusnendar; R. Abu Sofyan (Economics Professional in Action (E-Profit), 2020)
This study aims to determine the effect of service quality and store layout on customer satisfaction in the Borma Permata Cimahi. The population used in this study was the visitors of Borma Permata Cimahi. The sampling technique used purposive sampling method with a total sample of 100 people. Data collection techniques using questionnaires that have been tested for validity and reliability. Data analysis techniques used to answer hypotheses using t test and f test and multiple determination test. The results of the study show that: (1) In the partial test t obtained for service quality is 2,962 greater than t table of 1,98, so it can be concluded that service quality has an effect on customer satisfaction. (2) The result of partial store layout test obtained t count of 2,975 greater than the value of t table of 1,98, so that it can be concluded that store layout has an effect on customer satisfaction in the Borma Permata Cimahi. (3) In simultaneous testing (f test) obtained F value calculated at 15,428 the value is greater than the value of F table of 3,09 so that it can be concluded, that service quality and store layouts simultaneously influence customer satisfaction in the Borma Permata Cimahi